2002
DOI: 10.2320/matertrans.43.1593
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical and Simulative Studies of Trench Filling Mechanisms in the Copper Damascene Electroplating Process

Abstract: The role of additives in copper electroplating baths in the damascene process has been investigated. We proposed a bottom-up filling model and confirmed it by comparing the experimental and simulation results. Janus Green B and Basic Blue 3 which absorb on the copper surface and suppress copper deposition were examined for additive use to improve filling capability. Damascene copper grew uniformly in the bath that contained Basic Blue 3. But it grew preferentially from the bottom of the trench for Janus Green … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 8 publications
(7 reference statements)
2
12
0
Order By: Relevance
“…Lee and Park [61] calculated the strain energy caused by PEG incorporation by assuming that PEG is segregated at the grain boundary, and they concluded that the stress exerted by incorporated PEG on Cu atoms in the deposit is a significant factor of self-annealing. This result corresponds to the finding reported by Haba et al [71] that JGB is consumed during electrodepositon. To further investigate the effect of incorporation of additives on self-annealing, carbon microanalysis of the Cu electrodeposits was performed with the combustion-infrared absorption method.…”
Section: Carbon Microanalysis Of Copper Electrodepositssupporting
confidence: 92%
“…Lee and Park [61] calculated the strain energy caused by PEG incorporation by assuming that PEG is segregated at the grain boundary, and they concluded that the stress exerted by incorporated PEG on Cu atoms in the deposit is a significant factor of self-annealing. This result corresponds to the finding reported by Haba et al [71] that JGB is consumed during electrodepositon. To further investigate the effect of incorporation of additives on self-annealing, carbon microanalysis of the Cu electrodeposits was performed with the combustion-infrared absorption method.…”
Section: Carbon Microanalysis Of Copper Electrodepositssupporting
confidence: 92%
“…Effect of JGB.-Haba et al 8 investigated the effect of JGB in the damascene copper electrodeposition without adding SPS. According to their report, the addition of JGB without SPS also achieves bottom-up filling when there is a suitable concentration gradient of JGB generated in a trench from the balance between the diffusion rate and the consumption rate of JGB.…”
Section: Effect Of Sps-mentioning
confidence: 99%
“…In contrast to the effect of SPS ͑described in the preceding section͒, JGB is reported to be consumed on the copper surface during the copper deposition. 8 Thus, within the trenches, where the supply of additives from the bulk of the solution is retarded as compared with the outside of the trenches, the consumption of JGB should lead to a decrease in JGB concentration. Although the inhibition became greater at higher concentrations of JGB, not only the overfill phenomenon but also the bottom-up growth was inhibited at high concentrations of JGB.…”
Section: Effect Of Sps-mentioning
confidence: 99%
See 1 more Smart Citation
“…2,3) A Cu filling process using electroplating is therefore needed to produce low-resistance, highly reliable Cu interconnects. Electroplating in comparison with electroless plating can provide higher deposition rate as well as electroplating solutions for copper deposition are more stable and easier to control.…”
Section: Introductionmentioning
confidence: 99%